The local medicinal plant knowledge in Kashmir Western Himalaya: a way to foster ecological transition via community-centred health seeking strategies - Muhammad Manzoor; Mushtaq Ahmad; Muhammad Zafar; Syed Waseem Gillani; Hamayun Shaheen; Andrea Pieroni; Abdullah Ahmed Al-Ghamdi; Mohamed Soliman Elshikh; Saddam Saqib; Trobjon Makhkamov; Khislat Khaydarov (BMC, 2023)
Abstract Background The mountainous region of Kashmir is a biodiversity hotspot, with diverse local communities and a rich cultural history linked to nature. Mountain ecosystems are highly vulnerable to climate change. This study emphasises the need to record the indigenous ethnoecological knowledge of wild plants used for the treatment of various ailments at higher elevations in remote areas where globalisation poses a threat to this traditional knowledge. Methods The field survey was carried out in 2020-2022, to collect data on wild medicinal plants. Informants were selected randomly to collect indigenous medicinal knowledge using semi-structured interviews and group discussions. Various quantitative indices were employed to evaluate ethnomedicinal data. Results A total of 110 medicinal plants belonging to 49 families were recorded in the study area. These medicinal plants are extensively used by local communities for the treatment of 20 major disease categories. Asteraceae was the dominant family contributing (9.09%) to medicinal plants, followed by Polygonaceae (8.18%), Apiaceae (7.27%), Lamiaceae (5.45%), and Ranunculaceae (5.45%). We observed 166 remedies were used for the treatment of various diseases in humans, and 9 remedies were used for animals. The most frequently used medicinal remedy was tea or decoction (30.91%). Among the medicinal plants, herbs (85.5%) were most frequently used by the local populations of Kashmir, whereas leaves (10.26%) were used for the treatment of various ailments. Out of 110 species, 31 were endemic, 15 of which are endemic to the Kashmir region and 16 to the Western Himalaya. The highest RFC value was reported for Allium humile (0.77), the highest UV value for Fritillaria cirrhosa (1.33), and the highest ICF value for gastro-intestinal/digestive disorders (0.85). Conclusions Local communities still rely on wild medicinal plants for primary healthcare. These communities retained valuable indigenous knowledge, which needs to be preserved for the conservation and sustainable utilisation of natural resources. Further field exploration is required to fully explore indigenous knowledge in the mountainous regions of Kashmir, and this knowledge has the potential to support the ongoing ecological transition.